Field validation of a semi-spherical Lagrangian drifter - M. Gasser (Scientia Marina, 2001)
We present the design and field validation for the performance of a Semi-spherical Lagrangian Drifter (SELD). The SELD is a low-cost, low-technology, home-made alternative to much more expensive commercial Lagrangian drifters. An analysis of the SELD configuration shows that its drag area ratio is as good as TRISTAR and holey-sock drifters. Field results in a situation of near solid rotation within an oceanic vortex confirm that SELD and holey-sock drifters have an almost identical behavior.